Trinidad and Tobago: Sancoche - (:unkn) unknown (Distributed by Unimax Distributors Ltd.,[Trinidad and Tobago], 2011)
The postcard shows Sancoche which is a Caribbean dish made with a variety of meats and vegetables such as cassava. A recipe for the dish is printed on the back of the postcard.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cooking, Caribbean; Formulas, recipes, etc.